Eksistensi Lembaga Pendidikan Islam dalam Meretas Potensi Konflik Sosial Budaya: Analisis Lembaga STAIN Sorong di Papua Barat - Nur, Indria (Al-Riwayah : Jurnal Kependidikan, 2018)
This article discusses the role of strategic education institutions in developing a harmonious, harmonious and peaceful life in a diverse society of religions, tribes and cultures. As educational institutions function to engage in social integration, it is deemed most potential to instill the attitudes and values of togetherness, unity, peace, respect and closeness among ethnic, racial, religious, and cultural diversity of learners and society. The results of this study show the efforts and strategies undertaken STAIN Sorong institutions in applying a multicultural-oriented education. Through the cultivation of the spirit of multiculturalism will be a medium of training and awareness for the younger generation to accept cultural, religious, racial, ethnic and difference needs among others and willing to live together peacefully, especially in Papua